Поле тяжіння українського формалізму (до проблеми контекстів формалізму в Україні) - Коваленко, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is devoted to the consideration of the contexts of origin and development of Ukrainian formalism. The gravitation field of Ukrainian formalism, the components of which are also Marxism, avant-garde, national ideology etc., and the system of communications between the components of formalism are examined.